Acute Neurological Care in the COVID-19 Era: The Pandemic Health System REsilience PROGRAM (REPROGRAM) Consortium Pathway - Bhaskar, Sonu; Sharma, Divyansh; Walker, Antony H.; McDonald, Mark; Huasen, Bella; Haridas, Abilash; Mahata, Manoj Kumar; Jabbour, Pascal (Frontiers in Neurology, 2020)
The management of acute neurological conditions, particularly acute ischaemic stroke, in the context of Coronavirus disease 2019 (COVID-19), is of importance, considering the risk of infection to the healthcare workers and patients and emerging evidence of the neuroinvasive potential of the virus. There are variations in expert guidelines further complicating the picture for clinicians in acute settings. In this light, there is a compelling need for further formulation of recommendations that compile these variations seen in the numerous guidelines present. Health system protocols for managing ongoing acute neurological care and intervention need consideration of safety and wellbeing of the frontline healthcare workers and the patients. We examine existing pathways and their efficacy to mitigate viral exposure to the healthcare workers and patients and synthesise a systemic approach to manage patients with acute neurological conditions in the COVID-19 scenario. Early experiences with a COVID-19 positive stroke patient treated with endovascular thrombectomy is presented to highlight the urgent need for adequate personal protective equipment (PPE) during acute neuro-interventional procedures.